Peri-implant soft and hard tissue condition after alveolar ridge preservation with beta-tricalcium phosphate/type I collagen in the maxillary esthetic zone: a 1-year follow-up study - Jurišić, Tamara; S. Milić, Marija; S. Todorović, Vladimir; Živković, Marko; Jurišić, Milan; Milić-Lemić, Aleksandra; Tihaček-Šojić, Ljiljana; Brković, Božidar (Vojnosanitetski pregled, 2021)
Background/Aim. Alveolar ridge dimensional alterations following tooth extraction in the anterior maxilla often result in an inadequate bone volume for a correct implant placement. In order to obtain optimal bone volume various bone graft substitutes have become commercially available and widely used for socket grafting. The aim of this study was to examine and compare long-term clinical outcomes of dental implant therapy in the maxillary esthetic zone, after socket grafting with beta-tricalcium phosphate (TCP) combined with collagen type I, either with or without barrier membrane and flap surgery, after a 12-month follow-up. Methods. Twenty healthy patients were allocated to either C group (beta-TCP and type I collagen without mucoperiosteal flap coverage) or C+M group (beta-TCP and type I collagen barrier membrane with mucoperiosteal flap coverage). Following clinical parameters were assessed: implant stability (evaluated by a resonance frequency analysis – RFA), periimplant soft tissue stability (sulcus bleeding index – SBI, Mombelli sulcus bleeding index – MBI, periimplant sulcus depth, keratinized gingiva width, gingival level) and marginal bone level at the retroalveolar radiograms. Results. Within C+M group, RFA values significantly increased 12 weeks after implant installation compared to primary RFA values. Comparison between investigated groups showed a significantly reduced keratinized gingiva width in the C+M group compared to the C group after 3, 6, 9 and 12 months. Comparison between groups revealed significantly lower gingival level values in the C+M group at 9th and 12th month when compared to the C group. Conclusion. Implant treatment in the anterior maxilla could be effective when using a 9 months alveolar ridge preservation healing with combined treatment with beta-tricalcium phosphate and type I collagen, with regard to the peri-implant soft and hard tissue stability.